การเปลี่ยนแปลงทางเศรษฐกิจการเมืองในชุมชนชนบท และการปรับตัวของชาวนา - ประภาส ปิ่นตบแต่ง Prapas Pintoptang (Journal of Social Development and Management Strategy, 2015)
บทคัดย่อ บทความนี้มีวัตถุประสงค์ที่จะวิเคราะห์ถึงการเปลี่ยนแปลงในชุมชนชนบทปัจจุบัน ซึ่งพบว่า ชาวบ้านได้ปรับตัวโดยการเปิดรับเทคโนโลยีการผลิตสมัยใหม่และการพึ่งพิงระบบเศรษฐกิจแบบเงินตราอย่างลึกซึ้ง พวกเขาเข้าไปเกี่ยวข้องกับระบบเกษตรเชิงพาณิชย์อย่างเข้มข้นและซับซ้อน คนชนบทจึงกลายเป็นคนพันธุ์ใหม่ที่มีการปรับตัวหลายมิติ พวกเขาจึงไม่ได้เป็นแค่กึ่งชาวนา-กึ่งกรรมกรเท่านั้น แต่มีวัฒนธรรมการบริโภค การรับรู้ข่าวสารการเมืองที่ไม่แตกต่างไปจากคนชั้นกลางในเขตเมือง แต่เนื่องจากชาวชนบทครอบครองที่ดินขนาดเล็ก ต้นทุนการผลิตสูง ราคาผลผลิตต่ำ และค่าใช้จ่ายในครัวเรือนที่สูงตามวัฒนธรรมการบริโภคแบบสมัยใหม่ ส่งผลให้พวกเขาตกอยู่ในสภาพ “จมน้ำ” หรือ “สำลักน้ำ” อันเกิดจากปัญหาของวิกฤตแห่งการยังชีพ” ความผุกร่อนของระบบเครือญาติ ระบบอุปถัมภ์ และสถาบันเดิม คนชนบทได้สร้างความสัมพันธ์แบบใหม่ที่ยึดโยงเข้ากับเครือข่ายทางการเมืองภายนอก ทั้งในระดับชาติและระดับท้องถิ่น เพื่อเป็นหนทางให้พวกเขาสามารถมีชีวิตรอดได้ คำสำคัญ: ชุมชนชนบท สังคมชาวนา คนพันธุ์ใหม่ผู้หลากหลายชีวิต วิกฤตเศรษฐกิจแบบพอยังชีพ Abstract This article analyzes the changes in rural communities at present. It was found that villagers have adapted themselves through adopting new technologies and depending on the monetary economic system deeply. They have also been involved in the system of commercial agriculture intensively and complicatedly. The rural dwellers have become a new species of polybians, who have adapted their lives in many dimensions. They are not only semi-peasant/semi-proletariats, as proposed by some academicians, but they—not different from middle-class urban dwellers—have adopted the modern culture of consumerism and have obtained access to political information. As a result of their small-scale farms, high production costs, and high household expenditures in accordance with modern consumerism culture, they have unavoidably “drowned” or “suffocated” because of subsistence problems. With the present decay of kinship relationships, the patronage system and traditional institutions, rural dwellers have created new relationships, linking themselves with networks of external politics, at both the national and local levels, in order to survive at a subsistence level. Keywords: Rural Communities, Peasant Society, Polybian, Subsistence Crisis